Professional Ethics and the Education of Engineers at the International Islamic University Malaysia - Ibrahim M. Zein (International Institute of Islamic Thought, 2016)
This article focuses on professional ethics for engineers and engineering students at the International Islamic University Malaysia(IIUM). Due to the phenomenological interest in the theory of value and its realization within the framework of the professional ethics of engineers in a particular educational institution, this research applies a methodic strategy to address two levels of discourse equally. Thus, the theoretical aspect utilizes the tools of textual strategies and content analysis, whereas the specific case of the IIUM’s engineering faculty serves as a source of my phenomenological reflections on professional ethics for engineers. Despite being based on a limited source of data, some of the phenomenological remarks might be useful for other institutions of higher learning, for the stand on the theory of value used here is for both the values’ universality and relationality to human beings or, more directly, both the universality and rationality of an ethical discourse. Although largely an Islamic interpretation, this article’s main contributions are how to overcome this predicament in ethical sensibility, ward off dismissive gestures, and distinguish between values and their realization in the everyday world. By this process, the human agent discovers, rather than makes, values and comes to understand that ethical sensibility is not about truth and falsehood, but about the person’s degree of realization.